The reception of newly appointed teachers in the school unit and their professional development - Κατσικάς Απόστολος (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2024)
This article examines the multifaceted trajectory of newly appointed teachers, clarifying the pivotal roles of various stakeholders in their professional integration and development. It underscores the importance of a holistic approach to inducting new teachers, highlighting the difficulties of their transition from academic training to real classroom dynamics. The principal role of school principals in shaping the institutional culture, the support and professional development functions of the Teachers’ Association, and the indispensable guidance offered by mentor-counselors are discussed in-depth. Furthermore, the article emphasizes the continuous nature of teacher professional development, advocating its targeted and relevant implementation, especially for new teachers. By synthesizing these perspectives, the research provides a comprehensive blueprint for educational institutions aiming to foster an environment conducive to their teaching staff’s development and long-term success.